Хронічний панкреатит та цукровий діабет - предиктори розвитку раку підшлункової залози - A. I. Sukhodolia; S. A. Sukhodolia; V. P. Mosiychuk; M. V. Makohonskyi (Клінічна хірургія, 2019)
Хронічний панкреатит та цукровий діабет - предиктори розвитку раку підшлункової залози